Learning through Practice: Teaching Empirical Software Engineering for Undergraduate Students - Greco, Ranya Duran; Desidério, Sofia Bento; Bandeira, Caio César Sousa; Marques, Anna Beatriz dos Santos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11268, 2025)
Empirical Software Engineering (ESE) is essential for understanding the benefits and limitations of existing software engineering solutions. The evidence obtained through experiments guides the evolution of this area and optimizes the use of effort in relevant research that solves real problems or gaps. In ESE teaching, the challenge arises of preparing future software engineers to plan, conduct, and analyze experiments. This article reports on an experience of teaching ESE to 54 undergraduate students in an elective course, using Active Learning. To this end, we describe the activities carried out during the course, and to understand the effect of Active Learning, we conducted a survey using an online questionnaire. Twenty-seven students from the class consented to take part in the survey. The results show that 77.7% of the respondents had little or no experience of ESE before the course. At the end of the course, around 88.2% reported greater confidence in carrying out research in the area. The hypothesis test showed a significant increase in knowledge of the course’s content, emphasizing the topics of surveys and empirical studies. Correlation analysis revealed that the perceived contribution of the course is positively associated with student motivation. Despite some challenges, the students highlighted the methodology applied as being of great value to their training and entry into the job market. The experience of using Active Learning to teach ESE showed that, as well as contributing to the students’ education, the methodology gave them more confidence and motivation, which suggests the importance of pedagogical approaches that are closer to practice.